Reprogrammed CRISPR-Cas13b suppresses SARS-CoV-2 replication and circumvents its mutational escape through mismatch tolerance - Mohamed Fareh; Wei Zhao; Wenxin Hu; Joshua M. L. Casan; Amit Kumar; Jori Symons; Jennifer M. Zerbato; Danielle Fong; Ilia Voskoboinik; Paul G. Ekert; Rajeev Rudraraju; Damian F. J. Purcell; et al. (Nature Communications, 2021)
Cas13b can be harnessed to target and degrade RNA transcripts inside a cellular environment. Here the authors reprogram Cas13b to target SARSCoV-2 transcripts in infected mammalian cells and reveal its resilience to variants thanks to single mismatch tolerance.